UNDER-THE-COAT CAR CREDIT SALES PRACTICES UNDER ISLAMIC ECONOMIC LAW: A STUDY AT THE IJONK JAYA MOBIL SHOWROOM IN ACEH BESAR REGENCY - Aulia Dhuhri Phonna; Nahara Eriyanti (JURISTA: Jurnal Hukum dan Keadilan, 2026)
The growing demand for motor vehicles has led to the emergence of informal car credit sales as an alternative form of financing that is easier and more flexible. This study aims to analyse the practice of private car credit sales, identify the factors underpinning it, and examine its compatibility with the principles of Islamic economic law. This study employs a qualitative approach using field research methods, with data collection techniques including interviews, observation, and documentation. The results indicate that these credit transactions are conducted directly between the seller and the buyer without involving formal financing institutions, based on simple agreements founded on trust. The primary factors underpinning this practice include ease of access, consumers’ economic circumstances, business strategies of the operators, and the influence of the social environment. A review of Islamic economic law indicates that these practices do not yet fully comply with the principles of contractual clarity, justice, and transparency, and thus potentially contain elements of gharar and legal uncertainty. Therefore, improvements are required in the transaction system through the drafting of clearer contracts and an enhanced public understanding of the principles of Islamic economic law to ensure fair, secure, and Sharia-compliant transactions.